2005
DOI: 10.1016/j.crte.2005.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Review on the use of natural cave speleothems as palaeoseismic or neotectonics indicators

Abstract: Collapses that affect cave speleothems have frequently been attributed to earthquakes, although this has not been proved. Observations after an earthquake and laboratory tests indicate that only slender speleothems break under coseismic solicitation. Other causes as subsidence, decompression and creeping of ice or cave sediments explain most of the breaks. Tectonics is also a major cause of speleothems breakages and it is possible to detect minute movements of faults. It seems possible to make the difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…The use of speleotectonics for the recognition of paleoearthquakes is highly debated in the literature both because there are many possible breakdown causes that must be discounted (e.g., Gilli, 2005) and because the required conditions to break speleothems, in terms of speleothems vulnerability and seismic input, are still unclear (e.g., Cadorin et al, 2001;Lacave et al, 2004). On the other hand, peculiar features, recognized in many caves worldwide, have been often linked to earthquake damages (e.g., Postpischl et al, 1991;Ferranti et al, 1997;Lemeille et al, 1999;Delaby, 2001;Forti, 2001;Kagan et al, 2005;Šebela, 2008;Panno et al, 2009;Bábek et al, 2015;Méjean et al, 2015), although specific paleoearthquakes identified in caves have been rarely constrained by independent data outside caves (Becker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of speleotectonics for the recognition of paleoearthquakes is highly debated in the literature both because there are many possible breakdown causes that must be discounted (e.g., Gilli, 2005) and because the required conditions to break speleothems, in terms of speleothems vulnerability and seismic input, are still unclear (e.g., Cadorin et al, 2001;Lacave et al, 2004). On the other hand, peculiar features, recognized in many caves worldwide, have been often linked to earthquake damages (e.g., Postpischl et al, 1991;Ferranti et al, 1997;Lemeille et al, 1999;Delaby, 2001;Forti, 2001;Kagan et al, 2005;Šebela, 2008;Panno et al, 2009;Bábek et al, 2015;Méjean et al, 2015), although specific paleoearthquakes identified in caves have been rarely constrained by independent data outside caves (Becker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses and comparison with other data (e.g., paleoseismological data collected along neighboring seismogenic sources) are crucial to better constrain the age of a paleoearthquake. On the other hand, seismothems-like features can be induced also by non-seismic processes such as human and animal presence, shocks due to mine blasting, cryogenic fracturing, gravitational collapses, creep movements of sediments, glacial intrusion and catastrophic floods (e.g., Gilli, 2005;Becker et al, 2012). Therefore, it is fundamental to consider more factors that can interact and rule out all other possible nonseismic causative processes.…”
mentioning
confidence: 99%
“…of previous studies have shown that such damage is indicative of active tectonics (e.g., Kashima, 1993;Gilli, 2005). Consequently, a range of geological, geomorphological, and in situ displacement data have been collected.…”
Section: The Use Of a Karstic Cave System In A Study Of Active Tectonmentioning
confidence: 99%
“…In recent years, this topic has increasingly gained interest of researchers and been the subject to many studies (e.g., Ford and Hill, 1999;Gilli, 1999;Forti, 2001;Angelova et al, 2003;Gilli, 2005;Becker et al, 2006;Gunn, 2006;Š ebela, 2008;Garduñ o-Monroy et al, 2011). In longitudinal sections of stalagmites, a sudden change in growth orientation is taken as evidence of possible paleoseismic activity (Postpischl et al, 1991;Forti, 2001;Gilli, 2005;Š ebela, 2008). In fact, deviations from vertical growth of stalagmites can be due to seismic activity, glacial intrusion, or anthropogenic impact.…”
Section: Introductionmentioning
confidence: 99%